WAYS TO INCREASE STUDENTS' MOTIVATION IN ENGLISH CLASSES - Turg`unova, Fazilat; Rustamova Shahnoza Abdurahimovna, (Журнал иностранных языков и лингвистики, 2023)
Our article covers effective ways to increase student motivation in English classes. It is well known that motivation plays a major role in learning a foreign language. When students are interested in learning, they easily overcome difficulties, become familiar with the material, and develop strong language knowledge and skills.